Image Segmentation by the Image Foresting Transform - Miranda, Paulo A.V.; Falcão, Alexandre X. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2007)
The “Image Foresting Transform” (IFT) reduces image processing problems into a minimum-cost path forest problem in a graph derived from the image. We present three new image operators based on the IFT for image segmentation. The first method extends and combines approaches based on fuzzy connectedness, reducing user involvement. The second combines the IFT with graph-cut measures to circumvent problems of the traditional graphcut approaches. The third handles the leaking problem of watershed-based approaches by pruning trees of the forest. The proposed methods run in lineartime, are extensive to multidimensional images, and the last two are also free of “ad-hoc” parameters, and require only internal seeds.